Long distance dispersal and pseudo-cryptic species in Gastrotricha: first description of a new species (Chaetonotida, Chaetonotidae, Polymerurus) from an oceanic island with volcanic rocks - Magpali, Letícia; Machado, Danilo R.P.; Araújo, Thiago Q.; Garraffoni, André R.S. (European Journal of Taxonomy, 2021)
The majority of meiofaunal organisms have limited abilities to disperse over long distances, yet they may still have disjointed distributions. Many studies have found evidence of long distance meiofauna dispersal due to passive transport by wind and/or animals that serve as vectors for these widespread distributions. Our research on an archipelago in northeast Brazil uncovered a species of freshwater gastrotrich that at first sight appeared to be a ‘cosmopolitanʼ species that had surpassed the connectivity constraint to occupy an island more than 350 km from the mainland. However, through an integrative approach using molecular sequences and morphology, we have uncovered evidence of a pseudo-cryptic species in this freshwater gastrotrich. Polymerurus insularis sp. nov. closely resembles its congeners and can easily be mistaken for similar species such as P. nodicaudus, a cosmopolitan gastrotrich. Unique to P. insularis sp. nov. are (1) a cuticular armature composed of simple spined scales with polygonal shape (Type 1 scales), (2) a single, spineless dorsal scale with a triangular shape located terminally next to the furca base (Type 2 scale), (3) a spineless zone composed by a patch lacking cuticular ornamentation and flat, rounded or polygonal scales without spines (Type 4 scales) (4) particular sets of terminal spined or keeled scales located both dorsally and ventrally around the furca base (Types 3, 5, 6, 7 and 8 scales). The presence of this species on a volcanic island is discussed, as is the relationship between pseudocryptism and dispersal in gastrotrichs and other meiofauna.